HARMONIOUS INTERMINGLING BETWEEN SCHOOL SUPERVISORY TEAM AND INDUSTRY TRAINING SPECIALISTS - Kusnadi KUSNADI (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2020)
Dual system, as a combined partnership in education between vocational schools and companies is a teeming phenomenon all-over the world. Indonesia is one of the countries that for sometimes has been practicing this system seriously using huge amount of resources all-over the nation. However, the result is not typical for different schools. Originally the researcher was interested in evaluating the implementation of Dual System Program, but after sometimes during qualitative data collection, the researcher was more interested in some important factors affecting the success of dual system. The study shifted to explore key success factors in implementing dual system at YKTB 2 vocational High School in Bogor Indonesia. Using a Discrepancy Evaluation Model (DEM) and beyond, the researcher evaluated the implementation of the System at the Vocational School in Bogor Indonesia and conclude that the success of implementation is very much depends on harmonious association of school supervisory activities and the capability of training specialist in the industry to translate the objective of vocational schools for providing graduates to work in several positions available in the economy.